2020
DOI: 10.1002/ccd.28984
|View full text |Cite
|
Sign up to set email alerts
|

SCAI cardiogenic shock classification after out of hospital cardiac arrest and association with outcome

Abstract: Objectives We aimed to validate the Society for Cardiovascular Angiography and Interventions (SCAI) classification to evaluate association with outcome in a real‐world population and effect of invasive therapies. Background Cardiogenic shock is common after Out of Hospital Cardiac Arrest (OOHCA) but is often multifactorial and challenging to stratify. Methods The SCAI shock grade was applied to an observational registry of OOHCA patients on admission to our center between 2012 and 2017. The primary end‐point w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…Schrage and colleagues have also validated the SCAI stage to predict 30‐day mortality in more than 1,000 consecutive patients presenting with CS or large acute myocardial infarction 18 . Pareek and colleagues applied the classification to 393 out‐of‐hospital cardiac arrest cases as well, showing similar predictive value of the SCAI Shock Stage 19 …”
Section: Discussionmentioning
confidence: 99%
“…Schrage and colleagues have also validated the SCAI stage to predict 30‐day mortality in more than 1,000 consecutive patients presenting with CS or large acute myocardial infarction 18 . Pareek and colleagues applied the classification to 393 out‐of‐hospital cardiac arrest cases as well, showing similar predictive value of the SCAI Shock Stage 19 …”
Section: Discussionmentioning
confidence: 99%
“…In a large study of unselected CS patients (n = 1004), SCAI classification system was independently associated with the 30-day survival as well [70]. The classification was also validated in the setting of out-of-hospital cardiac arrest [71].…”
Section: Definitions and Classificationsmentioning
confidence: 99%
“…[106] Several studies have validated the SCAI classification in the acute settings. [106][107][108][109][110][111][112] Jentzer et al [107] retrospectively investigated the construct validity of the SCAI classification at the time of cardiac intensive care unit admission and found a robust association between the SCAI CS stages and hospital mortality in heterogenous critically ill patients (n = 10,004). Upon further analysis of the hospital survivors (n = 9,096), [108] the aforementioned group demonstrated that the SCAI classification at admission predicted the post-discharge mortality as well.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, they found that the reassessment of SCAI stage at 24 hours has refined the prognosis. The SCAI shock classification has also been validated retrospectively in specific subsets of patients i.e., after out of hospital cardiac arrest (n = 393) [111] and AMI (n = 300). [112] Additionally, from an analysis of a nationwide registry, Thayer and colleagues have validated the SCAI classification in the prediction of in-hospital mortality in patients presenting with CS (n = 1,414).…”
Section: Accepted Manuscriptmentioning
confidence: 99%